Lightning Current on the Frequency-Dependent Lumped Parameter Model Representing Short Transmission Lines - Sajid Leon Colqui, Jaimis [UNESP]; Carlos Timana, Luis; Kurokawa, Sergio [UNESP]; Ricardo Justo De Araujo, Anderson; Pissolato Filho, Jose (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The purpose of this paper is to investigate the performance of the Frequency-Dependent Lumped Parameter Model (FD-LPM) to adequately represent two distinct overhead transmission lines (OHTLs) subjected to different lightning currents. Frequency-Dependent Lumped Parameter Model (FD-LPM) takes into account the Skin and ground-return effects required to properly represent an OHTL and to compute the electromagnetic transients in power system. The FD-LPM is ruled by state equations in which the longitudinal parameters can be adjusted by a rational function using the Vector Fitting Technique and extended to any Electromagnetic Transient (EMT)-type simulators First, longitudinal impedances of these OHTLs are fitted into a rational function in residue-pole form which are incorporated in the ATPDraw software by the component LIB. Then, time domain responses due to lightning currents are computed under different scenarios. The FD-LPM was employed to represent short lines subjected to lightning strikes whose time domain responses were computed to different step sizes. Furthermore, results were compared with the JMarti's model for and those computed by Numerical Laplace Transform (NLT). Numerical results demonstrate that transient responses obtained with FD-LPM under small step size present a good agreement with those computed by NLT, which are assumed as reference responses.
Keywords: Electromagnetic transients; Lumped parameter model; Time step; Transmission lines